The importance of the cognitive environment for intertemporal choice - Michael A. Kuhn; Peter Joseph Kuhn; Marie-Claire Villeval (Institute for the Study of Labor (IZA), 2013)
We experimentally manipulate two aspects of the cognitive environment, cognitive depletion and recent sugar intake, and estimate their effects on individuals' time preferences in a way that allows us to identify the structural parameters of a simple (α,β,δ) intertemporal utility function for each person. We find that individuals exposed to a prior cognitive load, individuals who consumed a sugared drink, and individuals who consumed a sugar-free drink all defer more income than a control group exposed to none of these conditions. Structural estimates show that all three effects are driven entirely by increases in the intertemporal price elasticity parameter (α). Together, our results suggest that at least for complex economic decisions like intertemporal financial choice, the 'attention/focusing' effect of both prior cognitively demanding activity and prior assignment of a primary reward can improve decision-making.
Keywords: C91; D90; 330; time preferences; self-control; depletion; sucrose; experiment